EFEK MEDIASI KEPUASAN DALAM HUBUNGAN ANTARA PERSEPSI RISIKO DENGAN KEPERCAYAAN PRODUK KOSMETIK HIJAU MEREK THE FACE SHOP - Wulansari, Chintia; Sri Suprapti, Ni Wayan (E-Jurnal Manajemen; Vol 4 No 4 (2015), 2015)
The purpose of this study is to determine the mediating effect of satisfaction in the relationship between the perception of risk with confidence green cosmetic products by using the object cosmetic brand The Face Shop. The study was conducted in Denpasar with a sample size of 120 customers cosmetic brand The Face Shop. Data was collected using a questionnaire survey method and analyzed by path analysis and Sobel test. The results of this study are negatively perceived risk to customer satisfaction, perceived risk negatively affect customer trust, satisfaction has positively influence on customer trust and satisfaction were significantly mediate the relationship between perceptions of risk with trust.   Keywords: Green Cosmetics , Satisfaction , Perceived Risk , Trust